Some pathologies and weaknesses of the drug reimbursement system in Poland (Economic and Political Thought, 2015)
The article is a theoretical and research study. The theoretical partpresents the characteristics of the drug reimbursement system in Poland. Theempirical part presents the results of empirical research designed to identifymain pathologies and weaknesses in the current practice of the system, withparticular regard to the pharmacy Rx medications retail and wholesale market.The paper thoroughly presents three of the six categories of weaknesses andpathologies diagnosed, based on the results of the empirical research, i.e.rewarding patients with the use of rebates and discounts mechanisms (i.e.drugs for a penny) for providing pharmacies with prescriptions; changes inthe price of the drug after its introduction/removal from the list of reimburseddrugs, which are disadvantageous to the public payer (and/or a patient);limiting the availability of medicines in the domestic market resulting fromlegal and illegal parallel export as a consequence of low official domesticprices, and wholesale and pharmacy margins. The results of the study havebeen used to formulate general conclusions regarding valid reasons toproceed with the improvements to the reimbursement system.